A sodium ion battery positive electrode material with high cycle performance and its application

By using polydopamine to coat graphene and depositing iron trioxide particles in the sodium ion battery positive electrode material, combining sodium dihydrogen phosphate, glucose, chromium and vanadium dopants, the problem of insufficient electrochemical performance of existing sodium ion battery positive electrode materials is solved, and higher cycling and magnification performance is achieved.

CN119240652BActive Publication Date: 2025-03-21无锡钠科能源科技有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411768599.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-21
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

The electrochemical performance of existing sodium ion battery cathode materials is insufficient, especially in terms of cycling performance and rate performance.

Method used

Using multi-layer graphene as the substrate, iron trioxide particles are coated by polydopamine and chemically deposited on its surface, combined with sodium dihydrogen phosphate, glucose, chromium dopants and/or vanadium dopants, the cathode material is prepared by grinding and high temperature calcination.

Benefits of technology

It significantly improves the circulation and rate performance of sodium ion batteries, and has excellent comprehensive electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to the technical field of battery positive electrode materials, specifically to a sodium ion battery positive electrode material with high cycle performance and its application. The present application uses multilayer graphene as a substrate, is coated with polydopamine, and then chemically deposits ferric oxide particles on its surface, and mixes it with sodium dihydrogen phosphate, glucose, chromium dopant and / or vanadium dopant as raw materials, grinds and calcines at high temperature to obtain a positive electrode material doped with chromium and / or vanadium. The cycle performance and rate performance of the sodium ion battery prepared by the positive electrode material are improved, and the comprehensive electrochemical performance is excellent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery positive electrode materials, and in particular to a sodium ion battery positive electrode material with high cycle performance and application thereof. Background Art

[0002] Lithium-ion batteries are one of the earliest secondary batteries in the world and are currently the most widely used secondary batteries. However, due to the gradual scarcity of lithium resources, the cost of lithium-ion batteries is becoming increasingly high. Therefore, researchers are committed to developing sodium-ion batteries in an attempt to replace lithium-ion batteries in some application areas.

[0003] In the research and development process of sodium ion battery materials, positive electrode materials are relatively popular products. The current positive electrode materials for sodium ion batteries on the market are generally transition metal oxides, Prussian blue and its analogues, and polyanionic compounds. Among them, polyanionic compounds have excellent structural stability and have become one of the main raw materials. How to improve the electrochemical properties of polyanionic positive electrode materials is one of the current technical problems that need to be solved urgently. Summary of the invention

[0004] The object of the present invention is to provide a sodium ion battery positive electrode material with high cycle performance and its application, so as to solve the problems raised in the above background technology.

[0005] In order to solve the above technical problems, the present invention provides the following technical solution: a method for preparing a positive electrode material for a sodium ion battery with high cycle performance, comprising the following steps:

[0006] Step (1): mixing polydopamine-coated graphene with deionized water, ultrasonically dispersing for 20-30 minutes, then adding sodium acetate and ferrous chloride, stirring and reacting in a water bath at 85-95° C. for 1.5-2.5 hours, collecting the product by centrifugation, washing and drying, and obtaining ferric oxide-loaded graphene;

[0007] Step (2): Mix sodium dihydrogen phosphate and deionized water, add glucose and ferric oxide loaded graphene, stir evenly, then add chromium dopant and / or vanadium dopant, ultrasonically disperse for 20-30 minutes, grind at 40-45°C for 30-40 minutes, then add anhydrous ethanol, continue grinding for 30-40 minutes, vacuum dry at 60-70°C, then transfer to a nitrogen environment, heat to 500-550°C at a heating rate of 3-4°C / min, and keep warm for 10-11 hours to obtain a sodium ion battery positive electrode material.

[0008] In a more optimized solution, in step (2), the mass ratio of the sodium dihydrogen phosphate and the ferric oxide loaded graphene is (1-1.1):1; the amount of glucose used is 4-5wt% of the total mass of the sodium dihydrogen phosphate and the ferric oxide loaded graphene.

[0009] In a more optimized solution, in step (2), the amount of the chromium dopant used is 4-6wt% of the total mass of sodium dihydrogen phosphate and ferric oxide loaded graphene; the chromium dopant is any one of chromium chloride, chromium nitrate, and chromium acetate.

[0010] In a more optimized solution, in step (2), the vanadium dopant is any one of sodium metavanadate and sodium orthovanadate; the amount of the vanadium dopant is 1-3wt% of the total mass of sodium dihydrogen phosphate and ferric oxide loaded graphene.

[0011] In a more optimized solution, when the chromium dopant and the vanadium dopant are added together, the mass ratio of the chromium dopant to the vanadium dopant is (1.7~1.9):1.

[0012] In a more optimized solution, in step (1), the mass ratio of the polydopamine-coated graphene, sodium acetate, and ferrous chloride is 1: (8-10): (4-5).

[0013] The most optimized solution is to prepare polydopamine-coated graphene in the following steps:

[0014] S1: dimethylformamide and deionized water are mixed and stirred evenly, expanded graphite is added, and the mixture is allowed to stand at 25-30°C for 20-24 hours, and ultrasonically dispersed for 2-3 hours. Each ultrasonic dispersion lasts for 30-60 minutes, and the interval time is 30-60 minutes to obtain a graphene dispersion.

[0015] S2: mixing dopamine hydrochloride and deionized water, stirring evenly to obtain a dopamine solution;

[0016] Dissolve Tris in deionized water, add hydrochloric acid (5mM) to prepare Tris-HCl buffer (10mM, pH 8.5); add graphene dispersion to Tris-HCl buffer, ultrasonically disperse for 30-40 minutes in an ice water bath, then add dopamine solution, stir and react at 60-65°C for 15-20 hours, collect the product by filtration, wash and dry to obtain polydopamine-coated graphene.

[0017] In a more optimized solution, the mass ratio of dimethylformamide to deionized water is 4:1; the concentration of the graphene dispersion is 2-3 g / L; the concentration of the dopamine solution is 4-5 g / L; and the mass ratio of the graphene dispersion to dopamine hydrochloride is 1:(1-1.5).

[0018] A more optimized solution is a sodium ion battery positive electrode material with high cycle performance prepared according to any of the preparation methods described above.

[0019] A more optimized solution is a sodium ion battery, which includes a sodium ion battery positive electrode material with high cycle performance described in the above method.

[0020] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0021] The present application discloses a sodium ion battery positive electrode material with high cycle performance and its application. The scheme uses multilayer graphene as a substrate, is coated with polydopamine, and then chemically deposits iron oxide particles on its surface, and mixes it with sodium dihydrogen phosphate, glucose, chromium dopant and / or vanadium dopant as raw materials, grinds and calcines at high temperature to obtain a positive electrode material doped with chromium and / or vanadium (Na4Fe x Cr y V z (PO4)2P2O7), the cycle performance and rate performance of the sodium ion battery prepared by this positive electrode material are improved, and the overall electrochemical performance is excellent.

[0022] In the present application, the scheme first ultrasonically disperses expanded graphite to form multilayer graphene, and then coats the surface of the multilayer graphene with polydopamine. The purpose is: on the one hand, the presence of polydopamine can improve the uniform deposition of ferric oxide on the graphene surface, and the distribution of subsequent positive electrode materials during in-situ generation is also more uniform; on the other hand, due to the presence of polydopamine, it will cooperate with glucose to inhibit the size of the positive electrode material on the graphene surface and avoid its agglomeration; at the same time, after subsequent high-temperature calcination, polydopamine and glucose are thermally decomposed to form a "sandwich" structure. The presence of the multilayer graphene substrate can provide a conductive substrate, and the structure of polydopamine-positive electrode material-glucose carbon film will greatly improve the electrochemical performance of the positive electrode material.

[0023] On this basis, the scheme also introduces chromium dopants and / or vanadium dopants. The introduction of chromium dopants and / or vanadium dopants can improve the charge and discharge performance of the product. This application discloses a variety of schemes. Scheme 1: only introduce chromium dopants; Scheme 2: chromium dopants and vanadium dopants are added in combination, and it is defined that "the vanadium dopant is any one of sodium metavanadate and sodium orthovanadate; the amount of the vanadium dopant is 1~3wt% of the total mass of sodium dihydrogen phosphate and ferric oxide loaded graphene, and the amount of the chromium dopant is 4~6wt% of the total mass of sodium dihydrogen phosphate and ferric oxide loaded graphene; the chromium dopant is any one of chromium chloride, chromium nitrate, and chromium acetate"; Scheme 3: when the chromium dopant and the vanadium dopant are added in combination, the mass ratio of the chromium dopant to the vanadium dopant is (1.7~1.9):1; among them, the cycle performance of the positive electrode material prepared under the parameters of Scheme 3 is the best. DETAILED DESCRIPTION

[0024] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] Embodiment 1: A method for preparing a positive electrode material for a sodium ion battery with high cycle performance, comprising the following steps:

[0026] Step (1): 20 mg of polydopamine-coated graphene is mixed with deionized water, and ultrasonically dispersed for 20 minutes. Then, 180 mg of sodium acetate and 90 mg of ferrous chloride are added, and the mixture is stirred and reacted in a water bath at 85° C. for 2.5 hours. The product is collected by centrifugation, washed and dried to obtain iron trioxide-loaded graphene; the mass ratio of the polydopamine-coated graphene, sodium acetate and ferrous chloride is 1:9:4.5.

[0027] The preparation steps of polydopamine-coated graphene are as follows:

[0028] S1: Dimethylformamide and deionized water are mixed, stirred evenly, expanded graphite is added, and the mixture is allowed to stand at 25°C for 24 hours, and ultrasonically dispersed for 2 hours. Each ultrasonic dispersion lasts for 60 minutes, and the interval time is 30 minutes to obtain a graphene dispersion liquid. The mass ratio of the dimethylformamide to deionized water is 4:1. The concentration of the graphene dispersion liquid is 2 g / L.

[0029] S2: 60 mg of dopamine hydrochloride and deionized water were mixed and stirred evenly to obtain a dopamine solution; the concentration of the dopamine solution was 5 g / L.

[0030] Dissolve Tris in deionized water, add hydrochloric acid (5mM), and prepare Tris-HCl buffer (10mM, pH 8.5); add 50mg of graphene dispersion to 100mL of Tris-HCl buffer, ultrasonically disperse for 30min in an ice-water bath, then add dopamine solution, stir and react at 60°C for 20h, collect the product by filtration, wash and dry, and obtain polydopamine-coated graphene. The mass ratio of the graphene dispersion to dopamine hydrochloride is 1:1.2.

[0031] Step (2): Mix sodium dihydrogen phosphate and deionized water, add glucose and ferric oxide loaded graphene, stir evenly, add chromium dopant, ultrasonically disperse for 20 minutes, grind at 45°C for 30 minutes, add anhydrous ethanol, continue grinding for 40 minutes, vacuum dry at 70°C, transfer to a nitrogen environment, heat to 550°C at a heating rate of 3°C / min, and keep warm for 10 hours to obtain a sodium ion battery positive electrode material.

[0032] The mass ratio of sodium dihydrogen phosphate and ferric oxide loaded graphene is 1.1:1; the amount of glucose is 5wt% of the total mass of sodium dihydrogen phosphate and ferric oxide loaded graphene. The amount of chromium dopant is 6wt% of the total mass of sodium dihydrogen phosphate and ferric oxide loaded graphene; the chromium dopant is chromium chloride.

[0033] Embodiment 2: A method for preparing a positive electrode material for a sodium ion battery with high cycle performance, comprising the following steps:

[0034] Step (1): 20 mg of polydopamine-coated graphene is mixed with deionized water, ultrasonically dispersed for 25 minutes, and then 180 mg of sodium acetate and 90 mg of ferrous chloride are added, stirred and reacted in a 90° C. water bath for 2 hours, the product is collected by centrifugation, washed and dried to obtain iron trioxide-loaded graphene; the mass ratio of the polydopamine-coated graphene, sodium acetate and ferrous chloride is 1:9:4.5.

[0035] The preparation steps of polydopamine-coated graphene are as follows:

[0036] S1: Dimethylformamide and deionized water are mixed, stirred evenly, expanded graphite is added, and the mixture is allowed to stand at 30°C for 22 hours, and ultrasonically dispersed for 2.5 hours. Each ultrasonic dispersion lasts for 60 minutes, and the interval time is 30 minutes to obtain a graphene dispersion liquid. The mass ratio of the dimethylformamide to deionized water is 4:1. The concentration of the graphene dispersion liquid is 2 g / L.

[0037] S2: 60 mg of dopamine hydrochloride and deionized water were mixed and stirred evenly to obtain a dopamine solution; the concentration of the dopamine solution was 5 g / L.

[0038] Dissolve Tris in deionized water, add hydrochloric acid (5mM), and prepare Tris-HCl buffer (10mM, pH 8.5); add 50mg of graphene dispersion to 100mL of Tris-HCl buffer, ultrasonically disperse for 35min in an ice-water bath, then add dopamine solution, stir and react at 65°C for 18h, collect the product by filtration, wash and dry, and obtain polydopamine-coated graphene. The mass ratio of the graphene dispersion to dopamine hydrochloride is 1:1.2.

[0039] Step (2): Mix sodium dihydrogen phosphate and deionized water, add glucose and ferric oxide loaded graphene, stir evenly, then add chromium dopant and vanadium dopant, ultrasonically disperse for 25 minutes, grind at 45°C for 30 minutes, then add anhydrous ethanol, continue grinding for 40 minutes, vacuum dry at 70°C, transfer to a nitrogen environment, heat to 550°C at a heating rate of 3°C / min, and keep warm for 11 hours to obtain a sodium ion battery positive electrode material.

[0040] The mass ratio of sodium dihydrogen phosphate and ferric oxide loaded graphene is 1.1:1; the amount of glucose used is 5wt% of the total mass of sodium dihydrogen phosphate and ferric oxide loaded graphene. The amount of chromium dopant used is 5.1wt% of the total mass of sodium dihydrogen phosphate and ferric oxide loaded graphene; the chromium dopant is chromium chloride. The vanadium dopant is sodium metavanadate; the amount of vanadium dopant used is 2.7wt% of the total mass of sodium dihydrogen phosphate and ferric oxide loaded graphene.

[0041] Embodiment 3: A method for preparing a positive electrode material for a sodium ion battery with high cycle performance, comprising the following steps:

[0042] Step (1): 20 mg of polydopamine-coated graphene is mixed with deionized water, and ultrasonically dispersed for 30 minutes. Then, 180 mg of sodium acetate and 90 mg of ferrous chloride are added, and the mixture is stirred and reacted in a water bath at 95° C. for 1.5 hours. The product is collected by centrifugation, washed and dried to obtain iron trioxide-loaded graphene; the mass ratio of the polydopamine-coated graphene, sodium acetate and ferrous chloride is 1:9:4.5.

[0043] The preparation steps of polydopamine-coated graphene are as follows:

[0044] S1: dimethylformamide and deionized water are mixed, stirred evenly, expanded graphite is added, and the mixture is allowed to stand at 30°C for 20 hours, and ultrasonically dispersed for 3 hours. Each ultrasonic dispersion lasts for 60 minutes, and the interval time is 30 minutes to obtain a graphene dispersion liquid. The mass ratio of the dimethylformamide to deionized water is 4:1. The concentration of the graphene dispersion liquid is 2 g / L.

[0045] S2: 60 mg of dopamine hydrochloride and deionized water were mixed and stirred evenly to obtain a dopamine solution; the concentration of the dopamine solution was 5 g / L.

[0046] Dissolve Tris in deionized water, add hydrochloric acid (5mM), and prepare Tris-HCl buffer (10mM, pH 8.5); add 50mg of graphene dispersion to 100mL of Tris-HCl buffer, disperse by ultrasound in an ice-water bath for 40min, then add dopamine solution, stir and react at 65°C for 15h, collect the product by filtration, wash and dry, and obtain polydopamine-coated graphene. The mass ratio of the graphene dispersion to dopamine hydrochloride is 1:1.2.

[0047] Step (2): Mix sodium dihydrogen phosphate and deionized water, add glucose and ferric oxide loaded graphene, stir evenly, then add chromium dopant and vanadium dopant, ultrasonically disperse for 30 minutes, grind at 45°C for 30 minutes, then add anhydrous ethanol, continue grinding for 40 minutes, vacuum dry at 70°C, transfer to a nitrogen environment, heat to 550°C at a heating rate of 3°C / min, and keep warm for 11 hours to obtain a sodium ion battery positive electrode material.

[0048] The mass ratio of sodium dihydrogen phosphate and ferric oxide loaded graphene is 1.1:1; the amount of glucose used is 5wt% of the total mass of sodium dihydrogen phosphate and ferric oxide loaded graphene. The amount of chromium dopant used is 5.5wt% of the total mass of sodium dihydrogen phosphate and ferric oxide loaded graphene; the chromium dopant is chromium chloride. The vanadium dopant is sodium metavanadate; the amount of vanadium dopant used is 2.9wt% of the total mass of sodium dihydrogen phosphate and ferric oxide loaded graphene.

[0049] Comparative Example 1: In Comparative Example 1, the ratio of the chromium dopant to the vanadium dopant was adjusted based on Example 3, and the other steps remained unchanged.

[0050] A method for preparing a positive electrode material for a sodium ion battery with high cycle performance comprises the following steps:

[0051] Step (1): 20 mg of polydopamine-coated graphene is mixed with deionized water, and ultrasonically dispersed for 30 minutes. Then, 180 mg of sodium acetate and 90 mg of ferrous chloride are added, and the mixture is stirred and reacted in a water bath at 95° C. for 1.5 hours. The product is collected by centrifugation, washed and dried to obtain iron trioxide-loaded graphene; the mass ratio of the polydopamine-coated graphene, sodium acetate and ferrous chloride is 1:9:4.5.

[0052] The preparation steps of polydopamine-coated graphene are as follows:

[0053] S1: dimethylformamide and deionized water are mixed, stirred evenly, expanded graphite is added, and the mixture is allowed to stand at 30°C for 20 hours, and ultrasonically dispersed for 3 hours. Each ultrasonic dispersion lasts for 60 minutes, and the interval time is 30 minutes to obtain a graphene dispersion liquid. The mass ratio of the dimethylformamide to deionized water is 4:1. The concentration of the graphene dispersion liquid is 2 g / L.

[0054] S2: 60 mg of dopamine hydrochloride and deionized water were mixed and stirred evenly to obtain a dopamine solution; the concentration of the dopamine solution was 5 g / L.

[0055] Dissolve Tris in deionized water, add hydrochloric acid (5mM), and prepare Tris-HCl buffer (10mM, pH 8.5); add 50mg of graphene dispersion to 100mL of Tris-HCl buffer, disperse by ultrasound in an ice-water bath for 40min, then add dopamine solution, stir and react at 65°C for 15h, collect the product by filtration, wash and dry, and obtain polydopamine-coated graphene. The mass ratio of the graphene dispersion to dopamine hydrochloride is 1:1.2.

[0056] Step (2): Mix sodium dihydrogen phosphate and deionized water, add glucose and ferric oxide loaded graphene, stir evenly, then add chromium dopant and vanadium dopant, ultrasonically disperse for 30 minutes, grind at 45°C for 30 minutes, then add anhydrous ethanol, continue grinding for 40 minutes, vacuum dry at 70°C, transfer to a nitrogen environment, heat to 550°C at a heating rate of 3°C / min, and keep warm for 11 hours to obtain a sodium ion battery positive electrode material.

[0057] The mass ratio of sodium dihydrogen phosphate and ferric oxide loaded graphene is 1.1:1; the amount of glucose is 5wt% of the total mass of sodium dihydrogen phosphate and ferric oxide loaded graphene. The amount of chromium dopant is 5wt% of the total mass of sodium dihydrogen phosphate and ferric oxide loaded graphene; the chromium dopant is chromium chloride. The vanadium dopant is sodium metavanadate; the amount of vanadium dopant is 3.5wt% of the total mass of sodium dihydrogen phosphate and ferric oxide loaded graphene.

[0058] Comparative Example 2: Comparative Example 2 was compared with Example 3, but no chromium dopant or vanadium dopant was added in Comparative Example 2, and the other steps remained unchanged.

[0059] A method for preparing a positive electrode material for a sodium ion battery with high cycle performance comprises the following steps:

[0060] Step (1): 20 mg of polydopamine-coated graphene is mixed with deionized water, and ultrasonically dispersed for 30 minutes. Then, 180 mg of sodium acetate and 90 mg of ferrous chloride are added, and the mixture is stirred and reacted in a water bath at 95° C. for 1.5 hours. The product is collected by centrifugation, washed and dried to obtain iron trioxide-loaded graphene; the mass ratio of the polydopamine-coated graphene, sodium acetate and ferrous chloride is 1:9:4.5.

[0061] The preparation steps of polydopamine-coated graphene are as follows:

[0062] S1: dimethylformamide and deionized water are mixed, stirred evenly, expanded graphite is added, and the mixture is allowed to stand at 30°C for 20 hours, and ultrasonically dispersed for 3 hours. Each ultrasonic dispersion lasts for 60 minutes, and the interval time is 30 minutes to obtain a graphene dispersion liquid. The mass ratio of the dimethylformamide to deionized water is 4:1. The concentration of the graphene dispersion liquid is 2 g / L.

[0063] S2: 60 mg of dopamine hydrochloride and deionized water were mixed and stirred evenly to obtain a dopamine solution; the concentration of the dopamine solution was 5 g / L.

[0064] Dissolve Tris in deionized water, add hydrochloric acid (5mM), and prepare Tris-HCl buffer (10mM, pH 8.5); add 50mg of graphene dispersion to 100mL of Tris-HCl buffer, disperse by ultrasound in an ice-water bath for 40min, then add dopamine solution, stir and react at 65°C for 15h, collect the product by filtration, wash and dry, and obtain polydopamine-coated graphene. The mass ratio of the graphene dispersion to dopamine hydrochloride is 1:1.2.

[0065] Step (2): Mix sodium dihydrogen phosphate and deionized water, add glucose and ferric oxide loaded graphene, stir evenly, ultrasonically disperse for 30 minutes, grind at 45°C for 30 minutes, add anhydrous ethanol, continue grinding for 40 minutes, vacuum dry at 70°C, transfer to a nitrogen environment, heat to 550°C at a heating rate of 3°C / min, and keep warm for 11 hours to obtain a sodium ion battery positive electrode material.

[0066] The mass ratio of the sodium dihydrogen phosphate and the ferric oxide loaded graphene is 1.1:1; the amount of glucose used is 5wt% of the total mass of the sodium dihydrogen phosphate and the ferric oxide loaded graphene.

[0067] Comparative Example 3: Comparative Example 3 was compared with Example 3, but polydopamine coating was not introduced in Comparative Example 3, and the other steps remained unchanged.

[0068] A method for preparing a positive electrode material for a sodium ion battery with high cycle performance comprises the following steps:

[0069] Step (1): dimethylformamide and deionized water are mixed, stirred evenly, expanded graphite is added, and the mixture is allowed to stand at 30° C. for 20 hours, and ultrasonically dispersed for 3 hours, wherein each ultrasonic dispersion lasts for 60 minutes and the interval time is 30 minutes, to obtain a graphene dispersion liquid; the mass ratio of dimethylformamide to deionized water is 4:1; and the concentration of the graphene dispersion liquid is 2 g / L.

[0070] Step (2): Sodium dihydrogen phosphate and deionized water are mixed, glucose and graphene dispersion are added, and the mixture is stirred evenly. A chromium dopant and a vanadium dopant are added, and the mixture is ultrasonically dispersed for 30 minutes. The mixture is ground at 45°C for 30 minutes, and anhydrous ethanol is added. The mixture is ground for 40 minutes. The mixture is vacuum dried at 70°C, and then transferred to a nitrogen environment. The mixture is heated to 550°C at a heating rate of 3°C / min and kept warm for 11 hours to obtain a positive electrode material for a sodium ion battery.

[0071] The mass ratio of sodium dihydrogen phosphate and graphene dispersion is 1.1:1; the amount of glucose is 5wt% of the total mass of sodium dihydrogen phosphate and iron oxide loaded graphene. The amount of chromium dopant is 5.5wt% of the total mass of sodium dihydrogen phosphate and iron oxide loaded graphene; the chromium dopant is chromium chloride. The vanadium dopant is sodium metavanadate; the amount of vanadium dopant is 2.9wt% of the total mass of sodium dihydrogen phosphate and iron oxide loaded graphene.

[0072] Detection experiment:

[0073] The positive electrode materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were assembled to obtain a 2025 type button battery. The assembly steps of the sodium ion battery were as follows: according to the mass ratio of positive electrode material: carbon black: PVDF being 8:1:1, the raw materials were mixed and N-methylpyrrolidone was added to prepare a slurry, and the slurry was coated on an aluminum foil, wherein the loading amount of the positive electrode material was 8 mg / cm 2 , vacuum dried at 120°C, and pressed into sheets to obtain electrode sheets. The electrode sheets were then transferred to a glove box filled with argon gas, with a metal sodium sheet as the negative electrode, a separator as WhatManDF / D, a filler as nickel foam, and an electrolyte as 1M NaClO4 / PC (5% FEC) to assemble into 2025-type button cells for subsequent testing.

[0074] The test was conducted in the voltage range of 1.7~4.3V, with 2 cycles of activation at 0.1C and 200 cycles at 0.2C. The first discharge specific capacity and capacity retention rate were tested and recorded. See Table 1 for specific data.

[0075] Table 1

[0076]

[0077] Conclusion: This application discloses a sodium ion battery positive electrode material with high cycle performance and its application. The scheme uses multilayer graphene as a substrate, is coated with polydopamine, and then chemically deposits ferric oxide particles on its surface, and mixes it with sodium dihydrogen phosphate, glucose, chromium dopant and / or vanadium dopant as raw materials, grinds and calcines at high temperature to obtain a positive electrode material doped with chromium and / or vanadium. The cycle performance and rate performance of the sodium ion battery prepared with the positive electrode material are improved, and the comprehensive electrochemical performance is excellent.

[0078] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a positive electrode material for a sodium ion battery with high cycle performance, characterized in that: The following steps are involved: Step (1): mixing polydopamine-coated graphene with deionized water, ultrasonically dispersing for 20-30 minutes, then adding sodium acetate and ferrous chloride, stirring and reacting in a water bath at 85-95° C. for 1.5-2.5 hours, collecting the product by centrifugation, washing and drying, and obtaining ferric oxide-loaded graphene; Step (2): Mix sodium dihydrogen phosphate and deionized water, add glucose and ferric oxide loaded graphene, stir evenly, then add chromium dopant and / or vanadium dopant, ultrasonically disperse for 20-30 minutes, grind at 40-45°C for 30-40 minutes, then add anhydrous ethanol, continue grinding for 30-40 minutes, vacuum dry at 60-70°C, then transfer to a nitrogen environment, heat to 500-550°C at a heating rate of 3-4°C / min, and keep warm for 10-11 hours to obtain a sodium ion battery positive electrode material; The preparation steps of polydopamine-coated graphene are as follows: S1: dimethylformamide and deionized water are mixed and stirred evenly, expanded graphite is added, and the mixture is allowed to stand at 25-30°C for 20-24 hours, and ultrasonically dispersed for 2-3 hours. Each ultrasonic dispersion lasts for 30-60 minutes, and the interval time is 30-60 minutes to obtain a graphene dispersion. S2: mixing dopamine hydrochloride and deionized water, stirring evenly to obtain a dopamine solution; Dissolve Tris in deionized water, add hydrochloric acid to prepare Tris-HCl buffer; add graphene dispersion to Tris-HCl buffer, disperse by ultrasonic in an ice-water bath for 30-40 minutes, then add dopamine solution, stir and react at 60-65°C for 15-20 hours, collect the product by filtration, wash and dry, and obtain polydopamine-coated graphene; In step (2), the amount of the chromium dopant is 4-6wt% of the total mass of sodium dihydrogen phosphate and ferric oxide loaded graphene; the chromium dopant is any one of chromium chloride, chromium nitrate, and chromium acetate; in step (2), the vanadium dopant is any one of sodium metavanadate and sodium orthovanadate; the amount of the vanadium dopant is 1-3wt% of the total mass of sodium dihydrogen phosphate and ferric oxide loaded graphene.

2. The method for preparing a sodium ion battery positive electrode material with high cycle performance according to claim 1, characterized in that: In step (2), the mass ratio of the sodium dihydrogen phosphate and the ferric oxide loaded graphene is (1-1.1):1; the amount of glucose used is 4-5wt% of the total mass of the sodium dihydrogen phosphate and the ferric oxide loaded graphene.

3. The method for preparing a sodium ion battery positive electrode material with high cycle performance according to claim 1, characterized in that: When the chromium dopant and the vanadium dopant are added together, the mass ratio of the chromium dopant to the vanadium dopant is (1.7-1.9):

1.

4. The method for preparing a sodium ion battery positive electrode material with high cycle performance according to claim 1, characterized in that: In step (1), the mass ratio of the polydopamine-coated graphene, sodium acetate and ferrous chloride is 1:(8-10):(4-5).

5. The method for preparing a sodium ion battery positive electrode material with high cycle performance according to claim 1, characterized in that: The concentration of the graphene dispersion is 2-3 g / L; the concentration of the dopamine solution is 4-5 g / L, and the mass ratio of the graphene dispersion to dopamine hydrochloride is 1:(1-1.5).

6. A sodium ion battery positive electrode material with high cycle performance prepared by the preparation method according to any one of claims 1 to 5.

7. A sodium ion battery, characterized in that: The sodium ion battery comprises a sodium ion battery positive electrode material with high cycle performance as described in claim 6.

Citation Information

Patent Citations

  • Ferric oxide-polydopamine-graphene composite material, preparation method and application thereof

    CN109741964A

  • Nitrogen-doped carbon-coated composite Na4Fe3 (PO4) 2P2O7 sodium ion battery positive electrode material and preparation method thereof

    CN118352495A